EFFECT OF RESULTS AND INFLATION ON THIRD PARTY FUNDS IN SHARIA COMMERCIAL BANKS AND SHARIA BUSINESS UNITS INFLUENCE OF RESULTS AND INFLATION ON THIRD PARTY FUNDS IN SHARIA COMMERCIAL BANKS AND SHARIA BUSINESS UNITS - rizka yani; azwar hamid; ihdi aini; sulaiman efendi (Institut Agama Islam Negeri Padangsidimpuan, 2021)
Third-party funds are fund collectors in the banking sector. Third party funds include current accounts, savings and deposits collected from the community. Third party funds always experience an increase but are not followed by revenue sharing and inflation that has fluctuated. The formulation of the problem in this study is whether the profit sharing and inflation have a partial and simultaneous effect on Third Party Funds in Sharia Commercial Banks and Sharia Business Units. The purpose of this study was to determine how much the effect of profit sharing and inflation on Third Party Funds in Sharia Commercial Banks and Sharia Business Units. The discussion in this study relates to Islamic banking and macroeconomics. The approach taken in this study relates to theories relating to revenue sharing, inflation and Third Party Funds. This research is a quantitative study, the source of the data is secondary with a series of times series of 72 samples. Data collection techniques are documentation and literature. Normality Test, Normality Test, Classical Assumption Test which includes Multicollinearity Test, Autocorrelation Test, Heteroscedasticity Test, Hypothesis Test which includes Partial Significant Test (tTest), Simultaneous Regression Coefficient Test (Ftest), Determination Coefficient Test, Multiple Linear Analysis. The results of this study indicate that partially the shares have -ttest ttable (-2.725 -1.667) which means that the results have a significant negative effect on DPK. And inflation has -ttest -ttable (-4,852 -1,667) which means that inflation has a significant negative effect on Third Party Funds. And profit sharing and inflation simultaneously affect the Third Party Fund. This is evidenced by the value of Fcount Ftable (48.966 3.13). R2 shows that the percentage of contribution of the influence of independent variables on the dependent variable is 58.7% and the remaining 41.3% is influenced or or explained by other variables not included in this research model.